Salbutamol‐induced electrophysiological changes show no correlation with electrophysiological changes during hyperinsulinaemic–hypoglycaemic clamp in young people with Type 1 diabetes. Issue 9 (16th June 2018) - Novodvorsky, P.; Bernjak, A.; Robinson, E. J.; Iqbal, A.; Macdonald, I. A.; Jacques, R. M.; Marques, J. L. B.; Sheridan, P. J.; Heller, S. R.
Abstract: Aims: Hypoglycaemia causes QT‐interval prolongation and appears pro‐arrhythmogenic. Salbutamol, a β2 ‐adrenoreceptor agonist also causes QT‐interval prolongation. We hypothesized that the magnitude of electrophysiological changes induced by salbutamol and hypoglycaemia might relate to each other and that salbutamol could be used as a non‐invasive screening tool for predicting an individual's electrophysiological response to hypoglycaemia. Methods: Eighteen individuals with Type 1 diabetes were administered 2.5 mg of nebulized salbutamol. Participants then underwent a hyperinsulinaemic–hypoglycaemic clamp (2.5 mmol/l for 1 h). During both experiments, heart rate and serum potassium (and catecholamines during the clamp) were measured and a high‐resolution electrocardiogram (ECG) was recorded at pre‐set time points. Cardiac repolarization was measured by QT‐interval duration adjusted for heart rate (QTc ), T‐wave amplitude (Tamp ), T‐peak to T‐end interval duration (Tp Tend ) and T‐wave area symmetry (Tsym ). The maximum changes vs. baseline in both experiments were assessed for their linear dependence. Results: Salbutamol administration caused QTc and Tp Tend prolongation and a decrease in Tamp and Tsym . Hypoglycaemia caused increased plasma catecholamines, hypokalaemia, QTc and Tp Tend prolongation, and a decrease in Tamp and Tsym . No significant correlations were found between maximum changes in QTc [ r = 0.15, 95% confidence interval (95% CI) −0.341 to 0.576; P = 0.553), Tp Tend ( r = 0.075, 95% CI −0.406 to 0.524; P = 0.767), Tsym ( r = 0.355, 95% CI −0.132 to 0.706; P = 0.149) or Tamp ( r = 0.148, 95% CI −0.347 to 0.572; P = 0.558) in either experiment. Conclusions: Both hypoglycaemia and salbutamol caused pro‐arrhythmogenic electrophysiological changes in people with Type 1 diabetes but were not related in any given individual. Salbutamol does not appear useful in assessing an individual's electrophysiological response to hypoglycaemia. What's new?: We explored β2 ‐agonist salbutamol inhalation to identify those at risk of abnormal cardiac repolarization during hypoglycaemia. We describe the electrophysiological effects of nebulized salbutamol and a hypoglycaemic clamp in people with Type 1 diabetes. We confirm that both salbutamol and hypoglycaemia have pro‐arrhythmogenic electrophysiological effects. The magnitude of electrophysiological changes induced by these two stimuli did not show any relationship as measured by a statistically significant correlation in any of the examined variables. An individual's electrophysiological response to inhaled salbutamol does not appear useful in predicting their electrophysiological response to hypoglycaemia.